Changes in the pattern of health beneficial omega 3 fatty acids during processing of sardine fish curry - Shalini, R.; Jeya Shakila, R.; Palani Kumar, M.; Jeyasekaran, G. (Indian Journal of Fisheries, 2018)
Sardine curry, a traditional Indian dish was prepared from Sardinella gibbosa (Bleeker, 1849) to examine the changes in fatty acid composition particularly of the omega 3 fatty acids, when subjected to cooking at varying time duration. The major fatty acids present in raw sardine were myristic, palmitic, stearic, oleic, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The dominant fatty acids in sardine curry boiled for 20 min and 30 min were lauric acid, myristic acid, oleic acid and linoleic acid which might have leached from the ingredients such as coconut and the cooking oil used for curry preparation. There was a reduction in EPA and DHA in the sardine curry. The leaching of EPA and DHA from sardine pieces into the gravy was negligible. Sardine pieces in curry retained almost half of the EPA and DHA that are found in raw sardine even after boiling for 20 and 30 min respectively.